Effect of self-paced active recovery and passive recovery on blood lactate removal following a 200 m freestyle swimming trial - Mota MR; Dantas RA; Oliveira-Silva I; Sales MM; Sotero RC; Venâncio PE; Teixeira Júnior J; Chaves SN; de Lima FD (Dove Medical Press, 2017)
Márcio Rabelo Mota,1,2 Renata Aparecida Elias Dantas,1,2 Iransé Oliveira-Silva,2 Marcelo Magalhães Sales,2,3 Rafael da Costa Sotero,2 Patrícia Espíndola Mota Venâncio,2 Jairo Teixeira Júnior,2 Sandro Nobre Chaves,4 Filipe Dinato de Lima4 1College of Education and Health Sciences, University Center of Brasília – UniCEUB, Brasília, 2College of Physical Education, UniEVANGÉLICA, Anápolis, Goiás, 3College of Physical Education, Universidade Estadual de Goiás - UEG, Quirinópolis, Goiás, 4College of Physical Education, University of Brasília – UnB, Brasília, Brazil Purpose: The aim of this study was to investigate the effect of self-paced active recovery (AR) and passive recovery (PR) on blood lactate removal following a 200 m freestyle swimming trial. Patients and methods: Fourteen young swimmers (with a training frequency of 6–8 sessions per week) performed two maximal 200 m freestyle trials followed by 15 minutes of different recovery methods, on separate days. Recovery was performed with 15 minutes of passive rest or 5 minutes of passive rest and 10 minutes of self-paced AR. Performance variables (trial velocity and time), recovery variables (distance covered and AR velocity), and physiological variables (blood lactate production, blood lactate removal, and removal velocity) were assessed and compared. Results: There was no difference between trial times in both conditions (PR: 125.86±7.92 s; AR: 125.71±8.21 s; p=0.752). AR velocity was 69.10±3.02% of 200 m freestyle trial velocity in AR. Blood lactate production was not different between conditions (PR: 8.82±2.47 mmol L−1; AR: 7.85±2.05 mmol L−1; p=0.069). However, blood lactate removal was higher in AR (PR: 1.76±1.70 mmol L−1; AR: 4.30±1.74 mmol L−1; p<0.001). The velocity of blood lactate removal was significantly higher in AR (PR: 0.18±0.17 mmol L−1 min−1; AR: 0.43±0.17 mmol L−1 min−1; p<0.001). Conclusion: Self-paced AR shows a higher velocity of blood lactate removal than PR. These data suggest that athletes may be able to choose the best recovery intensity themselves. Keywords: athletic performance, fatigue, acidosis, anaerobic, metabolic response, sports